Indigenizing prisons: a Canadian case study - Tetrault, Justin E.C. (Crime and justice, 2022)
Mass incarceration of Indigenous peoples is a fundamental Canadian human rights problem. One response since the 1970s has been to “Indigenize” prisons by teaching Indigenous culture and history, facilitating spirituality, involving Elders and communities in rehabilitation, and creating special prisons called “healing lodges.” Criminologist proponents of “critical prison studies” are widely dismissive of these programs, with some arguing that Indigenized programming advances cultural genocide. They are wrong. University of Alberta Prison Project researchers interviewed nearly 600 prisoners in six prisons across western Canada, of whom 40 percent self-identified as Indigenous. Respondents generally praised Indigenizing initiatives for teaching them about their history and culture and helping them feel empowered and proud of their Indigenous identity. They said the initiatives helped them feel better able to cope with colonial traumas, including residential school and foster care system experiences; created a support network between Elders and fellow prisoners; and facilitated basic religious accommodation. Respondents’ criticisms focused on prison management, particularly security restrictions and staff prejudice that can prevent access to Indigenized resources. Indigenized programming supports the dignity and religious rights of incarcerated Indigenous peoples. Participants wanted expanded, more easily accessible cultural programming.